LC-MS/MS based targeted metabolomics method for analysis of serum and cerebrospinal fluid - Plewa, Szymon; Dereziński, Paweł; Florczak-Wyspiańska, Jolanta; Popławska-Domaszewicz, Karolina; Kozubski, Wojciech; Sokół, Bartosz; Jankowski, Roman; Matysiak, Jan; Kokot, Zenon J. (Journal of Medical Science, 2019)
Introduction. Recent instrumentation and software advancement enabled to develop new, high‑throughput targeted metabolomics methods for in‑depth exploration of metabolome in a quantitative manner. Material and Methods. The presented targeted metabolomics approach allows to analyze both of serum and CSF in the same way, with identical sample preparation procedures. The analyses were carried out using high‑performance liquid chromatography system coupled to triple quadrupole tandem mass spectrometer with electrospray ion source (LC‑ESI‑QqQ‑MS/MS). Results. The applied targeted metabolomics approach enabled to determine a wide panel of metabolites from different chemical classes of compounds including: acylcarnitines, amino acids and biogenic amines, glycerophospholipids, sphingolipids and sum of hexoses. Finally, 148 metabolites in serum and 57 in cerebrospinal fluid were determined. Conclusions. Here we presented the results of successful implementation of the method of analysis of low‑molecular weight compounds in human serum and CSF using targeted metabolomics. The evaluation of selected groups of metabolites resulted in obtaining the mean concentrations of panel of metabolites in serum and CSF, which gives a valuable information about the metabolome of these matrices.